Imagining Manila's future: Advertising's ideals for postwar reconstruction. (June 2022) - Hogben, Paul
Abstract : This article examines the role played by commercial advertising in promoting images of city reconstruction and architectural modernity within Manila in the years immediately following the end of the Second World War. It concentrates on the leading English-language daily, the Manila Times, which, from early 1946, began publishing advertisements that featured dramatic images of a future city of skyscrapers and other buildings rising out of the ruins of war. Advertisers called out to readers to contribute to the process of economic recovery by purchasing newly arrived shipments of goods and equipment and to support their efforts to drive property investment and the reconstruction of the city. By 1947 publicity was extending into home construction and advertisements incorporated illustrations of modernist houses as a means of promoting imported building products from the United States as well as locally manufactured materials. The article examines these advertisements for what they reveal about the stimulation of public interest in urban and architectural modernity within the Philippines in the early postwar years.